2017
DOI: 10.1111/ijcp.12970
|View full text |Cite
|
Sign up to set email alerts
|

Impact of binge eating disorder on functional impairment and work productivity in an adult community sample in the United States

Abstract: SummaryAimThis study compared functioning and productivity in individuals meeting Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM‐5) diagnostic criteria for binge eating disorder (BED) to those without BED.MethodsA sample of US adults from the National Health and Wellness Survey completed an Internet survey in October 2013. In addition to BED diagnostic criteria, the survey assessed functional impairment and productivity, respectively, using the Sheehan Disability Scale (SDS) and Work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 19 publications
3
29
0
Order By: Relevance
“…However, we believe that the increased availability of spare time for students who do not work may have influenced the greater frequency of use of strategies to increase muscle tone. Meanwhile, the significant path between work and binge eating has been discussed in recent studies 39 that reported work as an activity that has relevance for people's eating patterns; students who work may have little time to prepare a more balanced diet, resulting in changes in food intake. Moreover, physical activity level was significant for BIBCI subscales in women and men, and this relationship is commonly reported in previous studies.…”
Section: Resultsmentioning
confidence: 99%
“…However, we believe that the increased availability of spare time for students who do not work may have influenced the greater frequency of use of strategies to increase muscle tone. Meanwhile, the significant path between work and binge eating has been discussed in recent studies 39 that reported work as an activity that has relevance for people's eating patterns; students who work may have little time to prepare a more balanced diet, resulting in changes in food intake. Moreover, physical activity level was significant for BIBCI subscales in women and men, and this relationship is commonly reported in previous studies.…”
Section: Resultsmentioning
confidence: 99%
“…This recurrent binge eating is a source of significant distress for individuals with bulimia nervosa and binge eating disorder (American Psychiatric Association, 2013;Mitchison et al, 2018), and the disorders are associated with functional impairment and lower health-related quality of life (Ágh et al, 2016;Pawaskar, Witt, Supina, Herman, & Wadden, 2017).…”
Section: Abstract: Oxytocin; Bulimia Nervosa; Binge Eating Disorder;mentioning
confidence: 99%
“…Around 30% of treatment-seeking obese people7–9 and up to 47% of bariatric surgery candidates have full or partial BED 1 10 11. While BED itself has considerable individual and societal costs,12 the combination of BED and obesity is associated with more severe obesity, greater medical and psychiatric comorbidity, greater functional impairment and perinatal complications 12–15. Treatments for BED and obesity are sub-optimally effective, with cognitive behavioural therapy (CBT)16 and some medications17 reducing binge eating and related psychopathology,1 and approximately 50%–60% of patients achieving abstinence from bingeing at the end of treatment18 with some sustained cessation at follow-up 19.…”
Section: Introductionmentioning
confidence: 99%